IMMUNOMODULATORY POTENTIAL OF PALLADIUM(II) COMPLEXES WITH (1E,6E)-1,7-BIS (3,4-DIMETHOXYPHENYL) HEPTA-1,6-DIENE-3,5-DIONE - FISCHER-FODOR, Eva; MIKLÁŠ, Roman; KRAUSZ, Ludovic Tibor; VIRAG, Piroska; MOLDOVAN, Daniela Cristina; PERDE SCHREPLER, Maria; BERINDAN-NEAGOE, Ioana; DEVÍNSKY, Ferdinand; MIKLÁŠOVÁ, Natalia (Studia Universitatis Babeș-Bolyai Chemia, 2015)
In chemotherapy, the metal-based cytotoxic drugs are invariable components of therapeutic protocols, despite the biologic drugs expansion. A current tendency is to design metal-based drugs with highest efficacy and limited toxicity on normal human cells implicated in immune response. Therefore we synthesized and characterized two palladium(II) complexes with (1E,6E)-1,7-bis(3,4-dimethoxypenyl)hepta-1,6-diene-3,5-dione, a curcuminoid like ligand; their cytotoxicity towards tumor cells was tested, and their expected impact on T and B lymphocytes was measured in vitro. The lymphocytes treatment with the free ligand, and with the two complexes 1 and 2, increased significantly the proportion of the T helper CD4 positive cell population, concomitant with the decrease of T effector CD8 positive cells. The B cells were not affected by 1, but 2 has a minor inhibitory effect on CD19+ and CD45RA+ cells. The cells function was tested through the compounds modulator effect on membrane markers CD25 and GITR, both being slightly down regulated by 2, compensating of CD4+ overexpression and CD8+ down regulation. Moreover, complex 1 displayed minimal interference with the cellular antitumor immunity, acting as a selective inhibitor of cancer cells growth.